The elements of representation in Hobbes : aesthetics, theatre, law, and theology in the construction of Hobbes's theory of the state - Brito Vieira, Mónica (Studies in the history of political thought ;, 2009)
Commentators have traditionally constructed Hobbes's thinking on representation too narrowly, as a self-contained area of his political theory. This book challenges this orthodoxy of Hobbes scholarship, which owes less to Hobbesa (TM)s thought than to contemporary preconceptions of what counts as political thinking. In her powerful and original analysis, MA3nica Brito Vieira mines neglected strands of Hobbes's theory of representation, and reinstates it in a much wider pattern of Hobbesa (TM)s theorizing about human thought and action in relation to widely varied images, roles and fictions. Th.